SOFSEM 2009: Theory and Practice of Computer Science 35th Conference on Current Trends in Theory and Practice of Computer Science, `pindlerov Ml<U+00fd>n, Czech Republic, January 24-30, 2009. Proceedings - Nielsen, Mogens.; Ku era, Antonn̕.; Miltersen, Peter Bro.; Palamidessi, Catuscia.; Toma, Petr.; Valencia, Frank. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 35th Conference on Current Trends in Theory and Practice of Computer Science, SOFSEM 2009, held in `pindleruv Ml<U+00fd>n, Czech Republic, in January 2009. The 49 revised full papers, presented together with 9 invited contributions, were carefully reviewed and selected from 132 submissions. SOFSEM 2009 was organized around the following four tracks: Foundations of Computer Science; Theory and Practice of Software Services; Game Theoretic Aspects of E-commerce; and Techniques and Tools for Formal Verification.